'The Stone Mother Revisited': A female group analytic reflection on working within male low-secure forensic inpatient settings in the United Kingdom. (December 2018) - Vosmer, Susanne
This reflective account offers a female group analytic perspective on working with male inpatients within low-secure forensic settings. Viewed through the metaphor 'Stone Mother', I suggest that this setting is especially challenging for female group analysts because of its paternalistic matrix and the unflattering portrayal of women as 'seductive temptress' or 'evil stepmothers' in our inherited cultural foundation matrix. Females and female bodies therefore evoke distinct transferences and projections. In the sexual and gendered matrix of violence on the forensic male ward, these may be particularly malignant due to the aetiology and perpetuation of violence in a male-dominated world of power relations. Clinical vignettes are presented to demonstrate the many challenges female group analysts face in this setting. These are analysed through the lens of group analytic concepts and practice. Gender expectations are problematized. I shall suggest that therapy groups can instil a sense of belonging, acting as anti-shaming strategy and make a difference. However, due to the complexity of the sexual and gendered dynamic matrix of violence, violence cannot be treated in isolation on forensic wards by a predominantly female workforce. It must be addressed globally through dialogues in communities and beyond. Group analysis could take on this challenge.